Pengarusutamaan Nilai-Nilai Islam Moderat Melalui Revitalisasi Pancasila dalam Pendidikan Islam - Sigit Priatmoko (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
The occurrence of socio-religious conflicts recently is mainly due to a failure in dialogue understanding of religion with a plural and multicultural Indonesia context. The actors behind the conflict are Islamic fundamentalist groups or groups who insist on their Islamic ideology. They demanded that Indonesia become an Islamic state by applying law and system of government in accordance with the shari'ah of Islam as a whole and comprehensive. On the other hand, Muslim groups belonging to mainstream Islamic organizations (Muhammadiyah and NU) and nationalists opposed it. As a result there was a clash of identities and ideologies at the same time. In order to maintain the moderate values ​​of Indonesian Islam, Islamic educational institutions are required to play their role in strengthening moderate Islam through the